The Association and Mediating Biomarkers of Serum Retinol in Influencing the Development of Type 2 Diabetes: A Prospective Cohort Study in Middle-Aged and Elderly Population - Pang, Xiuyu; Yang, Sen; Guo, Xiaoyu; Li, Hongyin; Zhang, Yingfeng; Wei, Chunbo; Wang, Yu; Sun, Changhao; Li, Ying (Frontiers in Nutrition, 2022)
The aims of this research are to elucidate whether serum retinol is associated with type 2 diabetes and to explore the underlying mechanisms of the association in a prospective cohort study. A total of 3526 diabetes-free participants aged 40 years or older were enrolled at baseline in 2010-2012. Multivariable logistic regression was adopted to evaluate the associations of serum retinol and dietary vitamin A (VA) intake with type 2 diabetes. Mediation analyses were used to reveal potential mediators in their associations. After a mean follow-up of 5.3 years, 280 incident cases of type 2 diabetes occurred. Serum retinol was positively associated with the incidence of type 2 diabetes. The multivariable-adjusted odds ratios (ORs) and 95% confidence intervals (CIs) for type 2 diabetes from the bottom to the top quintile of serum retinol were 1.000, 1.878 (1.202, 2.936), 2.110 (1.364, 3.263), 1.614 (1.027, 2.538) and 2.134 (1.377, 3.306) (p-trend = 0.009), respectively. Mediation analysis showed that increased HOMA-IR, TG and serum xanthine oxidase (XO) activity could account for 8.5%, 14.7 and 12.1% of the total effects of serum retinol on type 2 diabetes, respectively. Serum retinol concentration was not significantly associated with dietary VA intake (r = -0.010, p-value = 0.570). In addition, no significant relationship was observed between dietary VA intake and the risk of type 2 diabetes. Overall, elevated serum retinol might increase the risk of type 2 diabetes which is mainly mediated by increased insulin resistance, TG or serum XO activity.